Quality of Online Learning Services in Graphic Design And Publishing Courses During The Covid-19 Pandemic - Bagus Yunianto Wibowo; Mellasanti Ayuwardani (IAIN Palopo, 2021)
The Covid-19 pandemic that has hit the entire world has caused all activities to be carried out online (online) including learning activities. Experience is lacking and is something that is still unfamiliar in Indonesia in conducting online learning, causing several obstacles and difficulties in delivering learning optimally, especially in practical courses. The problem of this research is